2019
DOI: 10.1039/c8cp07486k
|View full text |Cite
|
Sign up to set email alerts
|

Combined static and dynamic intramicellar fluorescence quenching: effects on stationary and time-resolved Stern–Volmer experiments

Abstract: It ain’t necessarily so—existing theories of combined quenching in micelles are flawed. We derive a consistent model, analyze its properties, and apply it to obtain information on ground-state complexes between fluorophore F and quencher Q.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…From Figure S8 (Supporting Information), it is evident that pristine ZnPc shows increased absorbance in the presence of nitrobenzene, in both the low-Q and high-Q regimes, while the conjugates do not show this trend. This observation is supportive of static quenching dynamics in pristine ZnPc, specifically in the low-Q regime, as the pure static or dynamic quenching mechanism is manifested in a linear relationship in the Stern–Volmer plot . However, in the low-Q regime, ZnPc@Na-CNC still showed this nonlinear behavior, where the I 0 / I vs Q plot is bending upward.…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…From Figure S8 (Supporting Information), it is evident that pristine ZnPc shows increased absorbance in the presence of nitrobenzene, in both the low-Q and high-Q regimes, while the conjugates do not show this trend. This observation is supportive of static quenching dynamics in pristine ZnPc, specifically in the low-Q regime, as the pure static or dynamic quenching mechanism is manifested in a linear relationship in the Stern–Volmer plot . However, in the low-Q regime, ZnPc@Na-CNC still showed this nonlinear behavior, where the I 0 / I vs Q plot is bending upward.…”
Section: Resultssupporting
confidence: 67%
“…However, in the low-Q regime, ZnPc@Na-CNC still showed this nonlinear behavior, where the I 0 / I vs Q plot is bending upward. Generally, an upward bending curve represents combined quenching . Therefore, in summary, we conclude that in pristine ZnPc, more static quenching occurs, particularly in the low-Q regime.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…It was found that the relationship of I 0 / I and UO 2 2+ quencher concentrations [UO 2 2+ ] represented a linear slope in the lower concentration range of UO 2 2+ , while the upward deviation from the linearity appeared with the increasing UO 2 2+ concentration. Previous studies have argued that such an upward curvature in the Stern–Volmer plot is interpreted as a combined static–dynamic quenching mechanism, instantaneous static quenching in pre-existing ground-state complexes between the fluorophore and quencher followed by slower dynamic quenching of those fluorophore molecules. If this combined static–dynamic quenching occurs for the complexation of the UO 2 2+ quencher with the PN-DCE fluorophore, the 1 H-NMR signals corresponding to 1:1 and 2:1 UO 2 2+ /PN-DCE complexes should have different chemical shifts. However, as shown in Figure (a), the 1 H-NMR peak area ratios changed depending on [UO 2 2+ ]/[PN-DCE], while each signal assigned to the 1:1 and 2:1 complexes was not distinguishable.…”
Section: Resultsmentioning
confidence: 99%